Does medical students' preference of test format (computer-based vs. paper-based) have an influence on performance? - Hochlehnert, Achim; Brass, Konstantin; Möltner, Andreas; Jünger, Jana (BMC medical education, 2011)
Computer-based examinations (CBE) ensure higher efficiency with respect to producibility and assessment compared to paper-based examinations (PBE). However, students often have objections against CBE and are afraid of getting poorer results in a CBE.
Gesehen am 04.08.2022